Analisis Persepsi Layanan Perbankan Elektronik Dihubungkan Dengan Faktor Kenyamanan, Komunikasi Dan Keamanan - Ronny Ronny (BIP's JURNAL BISNIS PERSPEKTIF, 2015)
Bank in organizing the internet banking service need to pay attention about customer perceptions to perform banking transactions through the website, such as customer perceptions regarding the safety, comfort, and communication. This study is aimed to analyze the customer perceptions on security, convenience, and communication aspects in the transactions use features which available in the banking website. As many as of 56 respondents who use Internet banking have filled out the questionnaire. The Results of study on bank customers responded by 4 bank staffs who understand internet banking. Qualitative analysis of the data has been obtained that the implementation of internet banking services which is reviewed by the safety, comfort, and communications aspects related to 5 main factors: the ability of technology, the ability of human resources bank, communication, internet banking procedures, and customer involvement.